Attenuation of allergic airway inflammation and hyperresponsiveness in a murine model of asthma by silver nanoparticles - Park, Hee Sun (Dove Medical Press, 2010)
The use of silver in the past demonstrated the certain antimicrobial activity, though this has been replaced by other treatments. However, nanotechnology has provided a way of producing pure silver nanoparticles, and it shows cytoprotective activities and possible pro-healing properties. But, the mechanism of silver nanoparticles remains unknown. This study was aimed to investigate the effects of silver nanoparticles on bronchial inflammation and hyperresponsiveness. We used ovalbumin (OVA)-inhaled female C57BL/6 mice to evaluate the roles of silver nanoparticles and the related molecular mechanisms in allergic airway disease. In this study with an OVA-induced murine model of allergic airway disease, we found that the increased inflammatory cells, airway hyperresponsiveness, increased levels of IL-4, IL-5, and IL-13, and the increased NF-κB levels in lungs after OVA inhalation were significantly reduced by the administration of silver nanoparticles. In addition, we have also found that the increased intracellular reactive oxygen species (ROS) levels in bronchoalveolar lavage fluid after OVA inhalation were decreased by the administration of silver nanoparticles. These results indicate that silver nanoparticles may attenuate antigen-induced airway inflammation and hyperresponsiveness. And antioxidant effect of silver nanoparticles could be one of the molecular bases in the murine model of asthma. These findings may provide a potential molecular mechanism of silver nanoparticles in preventing or treating asthma.